“When you use tramadol, the sperms will not come out. . .”: Unconventional strategies for avoiding unintended pregnancy among adolescents in Ghana - Gyan, S.E.; Boafo, I.M. (SAGE Open Medicine, 2024)
Background: In spite of adolescents’ high knowledge about modern contraceptives, usage is low especially in sub-Saharan Africa. Little is known about what adolescents use in place of modern contraceptive methods. Objective: This paper discusses lay strategies that adolescents use in their quest to prevent unintended pregnancy. Methods: A qualitative approach was used in the study reported in this paper. The paper draws on focus group data from a larger study looking at adolescent contraceptive needs in Ghana. A purposive sampling technique was used to select 79 adolescents who participated in a focus group discussion. Eight focus group discussions were held with both male and female adolescents aged 15–19. The data were analysed using the inductive thematic analysis method after transcribing the data. Results: We found that after having sex without using condom, adolescent girls ejected sperms by using water, salt solution or ice cubes, while others engaged in pushing with pelvic floor muscles. In their bid to prevent pregnancy, for boys, engaging in masturbation and the intake of Tramadol before sex was observed. When these lay strategies fail, adolescents resorted to unsafe and illegal abortion. Conclusions: Though adolescents girls engaged in unprotected sex, they still tried to avoid pregnancy, and consequently adopted lay strategies of pregnancy prevention that do not expose them to stigma. It is therefore recommended that the Ministry of Health through the Ghana Health Service consider establishing more adolescent-friendly health centres and expanding existing ones where adolescents could easily visit to have their sexual and reproductive health needs addressed in a very confidential and non-judgemental manner
Research Article
Keywords: Contraceptive; unintended pregnancy; abortion; masturbation; tramadol; Ghana